Femoro-femoral arterial bypass is an effective and durable treatment for symptomatic unilateral iliac artery occlusion. - Pai, M; Handa, A; Hands, L; Collin, J (2003)
AIMS: This study was designed to determine the effectiveness of femoro-femoral arterial bypass (FFB) operation at hospital discharge and 1 year after operation, and to determine the role of long saphenous vein (LSV) as a conduit. METHODS AND RESULTS: A retrospective review was undertaken of 161 consecutive patients (median age, 66 years; range, 44-97 years) who had femoro-femoral grafts during the 12 years from July 1987 to March 1999. The indication for operation was claudication in 66 patients and critical ischaemia in 95. A synthetic graft was used in 123 patients and LSV in 38. Six patients with LSV had a previously infected synthetic graft and 2 a previously occluded synthetic graft. In-hospital operative mortality was 13 (8.1%). One year postoperatively, known mortality was 29, fifteen patients were lost to follow-up putting 1-year mortality at 18.0-27.3%. Eight of these had LSV as the conduit. At discharge from hospital, the median improvement in the ankle brachial pressure index was 0.3 (range, 0-1.0) overall, and 0.32 for patients with LSV (range 0-1.0). Among the 117 known survivors at 1 year, secondary graft patency was 107 confirmed by Doppler or duplex (91.5%) overall, and 25 (89.3%) for LSV; 100 (85.5%) maintained symptomatic improvement, 11 (9.4%) were experiencing no benefit and 6 (5.1%) were worse, of whom 2 had undergone amputation. In patients in whom LSV was used, 22 (78.8%) remained symptomatically improved, 3 (10.7%) experienced no benefit, 3 deteriorated and one had an amputation. CONCLUSIONS: One year following FFB, at least 18.0% of patients were dead. Among possible survivors to 1-year, graft patency was at least 78.8% and at least 75.8% remained clinically improved. FFB is effective in the treatment of unilateral iliac artery occlusion. LSV is as effective as a synthetic conduit.